The Stability Improvement of Aspergillus fumigatus α-Amylase by Immobilization onto Chitin-Bentonite Hybrid - Ezra Rheinsky Tiarsa; Yandri Yandri; Tati Suhartati; Heri Satria; Bambang Irawan; Sutopo Hadi (Biochemistry Research International)
Enzyme immobilization is a powerful method to improve the stability, reuse, and enzymatic properties of enzymes. The immobilization of the α-amylase enzyme from Aspergillus fumigatus on a chitin-bentonite (CB) hybrid has been studied to improve its stability. Therefore, this study aims to obtain the higher stability of α-amylase enzyme to reduce industrial costs. The procedures were performed as follows: production, isolation, partial purification, immobilization, and characterization of the free and immobilized enzymes. The CB hybrid was synthesized by bentonite, chitin, and glutaraldehyde as a cross-linker. The free enzyme was immobilized onto CB hybrid using 0.1 M phosphate buffer pH 7.5. The free and immobilized enzymes were characterized by optimum temperature, Michaelis constant (KM), maximum velocity Vmax, thermal inactivation rate constant (ki), half-life (t1/2), and transformation of free energy because of denaturation (ΔGi). The free enzyme has optimum temperature of 55°C, KM = 3.04 mg mL−1 substrate, Vmax=10.90 μmolemL−1min−1, ki = 0.0171 min−1, t1/2 = 40.53 min, and ΔGi = 104.47 kJ mole−1. Meanwhile, the immobilized enzyme has optimum temperature of 60°C, KM = 11.57 mg mL−1 substrate, Vmax=3.37 μmolemL−1min−1, ki = 0.0045 min−1, t1/2 = 154.00 min, and ΔGi = 108.17 kJ mole−1. After sixth cycle of reuse, the residual activity of the immobilized enzyme was 38%. The improvement in the stability of α-amylase immobilized on the CB hybrid based on the increase in half-life was four times of the free enzyme.